Empowering The Magersaren Community: Technology Dissemination For Ground Coffee Added Value Improvement - Dewi, Ika Atsari (Journal of Innovation and Applied Technology, 2022)
The Magersaren community are farmers and forest workers who depend on forest for their livelihoods. Magersaren has been practicing agroforestry for a long time. They grow Robusta and Arabica coffee among other forest plants. Currently coffee is a favorite beverage, the number of its consumers continues to increase. The execution of community service activities that have been carried out consists of: 1)program socialization; 2)focus group discussion; 3)production, packaging and management training; 4)small-business starting up; 5)program evaluation. These community service activities are held during the social distancing due to the COVID-19 pandemic. This condition becomes an obstacle to the effectiveness of program implementation. The start-up small business needs to be continuously supported in order to survive through a critical period of business development, especially under economic pressure during the pandemic.